Pengaruh Sifat Fisik Terhadap Nilai Uniaxial Compressive Strength Batuan Dengan Kondisi Natural, Jenuh dan Kering Pada Formasi Balikpapan dan Pulaubalang Provinsi Kalimantan Timur - Firman Firman; Albertus Juvensius Pontus; Lucia Litha Respati (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
The uniaxial compressive strength value is one of the important parameters that is widely used in rock engineering projects in determining rock mass. The strength of rocks is greatly influenced by the water content and degree of saturation in the rock. Reduction of strength in rock is associated with an increase in water content, a slight increase in water content will cause a significant deviation in the compressive strength test value.This research is quantitative research, so to obtain accurate calculation data, testing methods are used in the form of compressive strength tests on rocks and physical properties tests in the treatment of samples of original rock, saturated rock and dry rock before testing. In this research, 2 types of rock were used, including limestone and sandstone in 2 rock formations, namely the Balikpapan formation and the Pulaubalang formation, so that the accuracy of the test result values ​​could be obtained well. Based on the results of observations and calculations that have been carried out, the water content values ​​of limestone in natural, saturated and dry conditions in the Balikpapan formation are obtained with average values ​​of 1.709%, 2.262% and 0.961% respectively. The water content of sandstone in natural, saturated and dry conditions is the Pulaubalang formation with average values ​​of 2.491%, 9.425% and 0.463% respectively. The UCS value of limestone in natural, saturated and dry conditions in the Balikpapan formation has an average value of 25.29 Mpa, 37.57 Mpa and 40.70 Mpa respectively. The UCS value of sandstone in natural, saturated and dry conditions in the Pulaubalang formation has an average value of 9,565 Mpa, 6,537 Mpa and 12,730 Mpa. It can be concluded that the correlation between uniaxial compressive strength values ​​and water content values ​​in limestone and sandstone shows a positive linear correlation, which means they have a strong relationship. The higher the compressive strength value of limestone and sandstone, the lower the water content value.